2007
DOI: 10.1007/s10393-007-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Ribeiroia Infection Is Not Responsible for Vermont Amphibian Deformities

Abstract: Reports of limb deformities in amphibians have garnered wide notice from scientists and the public alike. Recent laboratory and field research has supported the hypothesis that infection by the helminth parasite, Ribeiroia ondatrae, is associated with deformities, particularly in the western United States. In this study, observational and experimental evidence from eastern United States (Vermont) provides evidence that Ribeiroia is absent from a large sample of sites including those with a history of relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Possible causes include parasites, predators, UV-B, and contaminants (reviewed in . The trematode parasite, Ribeiroia ondatrae is an established cause of abnormalities where it occurs , but there are places where abnormal frogs are frequent but this parasite is not detected (Skelly et al 2007, Reeves et al 2008. High frequencies of abnormalities in sites lacking R. ondatrae have been correlated with aquatic predators, which may amputate the developing limbs of tadpoles as they prey on them Sessions 2009, Bowerman et al 2010), Reeves et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Possible causes include parasites, predators, UV-B, and contaminants (reviewed in . The trematode parasite, Ribeiroia ondatrae is an established cause of abnormalities where it occurs , but there are places where abnormal frogs are frequent but this parasite is not detected (Skelly et al 2007, Reeves et al 2008. High frequencies of abnormalities in sites lacking R. ondatrae have been correlated with aquatic predators, which may amputate the developing limbs of tadpoles as they prey on them Sessions 2009, Bowerman et al 2010), Reeves et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other research suggests that missing limb deformities may be caused by predation (Martof, '56;Veith and Viertel, '93;Bohl, '97;Sessions, 2003;Eaton et al, 2004), but this possibility has not been well studied experimentally and is considered doubtful by some researchers (e.g. Meteyer et al, 2000;Skelly et al, 2007;Lannoo, 2008). Here we present results of a 1 Some researchers refer to these abnormalities as ''malformations'' (e.g.…”
mentioning
confidence: 95%
“…Recent research has resolved several different categories of deformed amphibians, suggesting different causes or combinations of causes ranging from chemical pollution and UV-B radiation to parasites and predation Ouellet, 2000;Johnson et al, 2001;Blaustein and Johnson, 2003;Sessions, 2003;Lannoo, 2008;Rohr et al, 2008). Although much research has focused on frogs with parasiteinduced supernumerary hind limbs (Sessions and Ruth, '90;Johnson et al, '99;Sessions et al, '99;Stopper et al, 2002;Schotthoefer et al, 2003;Johnson et al, 2004), the vast majority of reports of deformed amphibians involve various species of frogs and toads with missing hind limbs, missing limb segments, or misshapen limbs, with no apparent involvement of parasites (Meteyer, 2000;Levey et al, 2003;Sessions, 2003;Skelly et al, 2007;Lannoo, 2008).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…ionising radiation or agricultural chemicals) causes of abnormalities and concluded that trematode-induced abnormalities are a minority of cases, largely restricted to the upper Midwest and parts of California in the USA. Frogs with abnormalities occur in some Vermont ponds without Ribeiroia obdatrae (Skelly et al 2007). Nearby agricultural areas are possible risk factors, but urban and suburban areas may be an even greater risk.…”
Section: Contaminantsmentioning
confidence: 99%